Mörk Materia (amplified 8mm performance) - Koutsomichalis, Marinos (My University, 2023)
Mörk Materia manifests in a number of different fashions with respect to the materials involved. Most notably it concerns: 35mm and 4×5″ film negatives (to be digitally scanned and/or printed in the darkroom); unique silver gelatin prints created directly on photo paper; and Supr8/8mm motion films to be projected. All silver gelatin prints (from films or directly onto paper) are unique creations stamped, numbered, and signed by the artist.